A pathological toe fracture as the first presentation of cervical cancer: A case report. Issue 3 (January 2019) - Zhang, Jinming; Li, Ze; Ma, Xiaotong; Feng, Helin
Abstract: Rationale: Cervical cancer is one of the most common gynecologic malignancies worldwide, and it spreads mainly through direct extension. Distinct metastases are less common and usually spread to distant lymph nodes, lungs, and bones. Bone metastases from cervical cancer are most commonly observed in the pelvis and spine. Thus, a pathological toe fracture as the initial presentation of cervical cancer is extremely rare. Patient concerns: We report a patient with a toe metastasis that first presented with pain caused by a pathological fracture. Diagnoses: The patient underwent surgery to remove the right great toe, and the histopathology revealed squamous carcinoma that originated from the cervix. Interventions: The patient then underwent cervical cancer surgery, chemotherapy, and radiotherapy. Lessons: A pathological toe fracture as the initial presentation of cervical cancer is extremely rare, but clinicians need to be aware that we should not exclude cancer when patients come to the hospital for pathological fractures.